PENGARUH LINGKUNGAN USAHA, PROFITABILITAS, PENEGAKAN HUKUM, DAN SANKSI TERHADAP KETIDAKPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA DUMAI - Mutia Hani; Yessi Mutia Basri; Al Azhar L ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine the effect of business environment, profitability, law enforcement, and punishment on individual taxpayer non compliance at the KPP Pratama Dumai. This study used purposive sampling method. The sample in this study is the individual taxpayer. Only 100 of 110 quetioner that had been distributed are back to be processed. The statistical method used to test the hypothesis of the research is multiple linear regression analysis using SPSS 20.0. The results showed that (1)business environment that has not impact on a individual tax payer noncompliance (2) profitability that has a impact on a individual tax payer noncompliance(3) law enforcement that has not impact on a individual tax payer noncompliance(4) punishment that has a impact on a individual tax payer noncompliance. The determination of coefficient (Adj-R2) in this meant that 42,2 %. And then 57,8% has impact by other variables.Keywords :Non-compliance with individual taxpayers, business environment, profitability,law enforcement and punishment.